A novel TMPRSS6 mutation that prevents protease auto-activation causes IRIDA - Altamura, Sandro; D'Alessio, Flavia; Selle, Barbara; Muckenthaler, Martina (Biochemical journal, 2010)
IRIDA (iron-refractory iron-deficiency anaemia) is a rare autosomal-recessive disorder hallmarked by hypochromic microcytic anaemia, low transferrin saturation and high levels of the iron-regulated hormone hepcidin. The disease is caused by mutations in the transmembrane serine protease TMPRSS6 (transmembrane protease serine 6) that prevent inactivation of HJV (haemojuvelin), an activator of hepcidin transcription. In the present paper, we describe a patient with IRIDA who carries a novel mutation (Y141C) in the SEA domain of the TMPRSS6 gene. Functional characterization of the TMPRSS6(Y141C) mutant protein in cultured cells showed that it localizes to similar subcellular compartments as wild-type TMPRSS6 and binds HJV, but fails to auto-catalytically activate itself. As a consequence, hepcidin mRNA expression is increased, causing the clinical symptoms observed in this IRIDA patient. The present study provides important mechanistic insight into how TMPRSS6 is activated.